2014
DOI: 10.3233/nre-141137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active pulmonary rehabilitation on pulmonary function in patients with brain lesion

Abstract: BACKGROUND: The patients with brain lesion have a high risk of pulmonary complication due to restrictive pulmonary impairment. OBJECTIVE: To investigate the effectiveness of active pulmonary rehabilitation on pulmonary functional improvement in these patients. METHODS: Twnety-two patients of hemiplegia or quadriplegia with brain lesion were recruited who had restrictive pulmonary impairment. The patients were randomly assigned to an experimental group that receive active pulmonary rehabilitation training and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…This study was undertaken to document the effects of Previous studies have shown that air stacking exercise significantly improves pulmonary function and peak cough flow in patients with restrictive pulmonary disease caused by a brain lesion (Na et al, 2014). In the present study, after 4 weeks of active pulmonary rehabilitation consisting of air stacking and a manually assisted cough exercise added to a conventional pulmonary rehabilitation program, FVC increased from 1.9 to 2.7 liters, FEV1 from 1.5 to 1.8 liters, and PCF increased to 349.1 liter/min in the experimental group, and all these increases were significant.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study was undertaken to document the effects of Previous studies have shown that air stacking exercise significantly improves pulmonary function and peak cough flow in patients with restrictive pulmonary disease caused by a brain lesion (Na et al, 2014). In the present study, after 4 weeks of active pulmonary rehabilitation consisting of air stacking and a manually assisted cough exercise added to a conventional pulmonary rehabilitation program, FVC increased from 1.9 to 2.7 liters, FEV1 from 1.5 to 1.8 liters, and PCF increased to 349.1 liter/min in the experimental group, and all these increases were significant.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…During the 4 weeks of the experiment, conventional pulmonary rehabilitation exercises, such as, cough exercise, deep breathing, and abdominal muscle strengthening exercises were performed (Na et al, 2014).…”
Section: ) Conventional Pulmonary Rehabilitationmentioning
confidence: 99%
See 3 more Smart Citations